Risk factors for short term thyroid dysfunction after hematopoietic stem cell transplantation in children - You Jin Jung; Yeon Jin Jeon; Won Kyoung Cho; Jae Wook Lee; Nack-Gyun Chung; Min Ho Jung; Bin Cho; Byung-Kyu Suh (Korean Pediatric Society, 2013)
PurposeThe purpose of this study was to evaluate short-term thyroid dysfunction and related risk factors in pediatric patients who underwent hematopoietic stem cell transplantation (HSCT) during childhood.MethodsWe studied 166 patients (100 boys and 66 girls) who underwent HSCT at the Catholic HSCT Center from January 2004 through December 2009. The mean age at HSCT was 10.0±4.8 years. Thyroid function of the patients was tested before and during 3 months of HSCT.ResultsOut of 166 patients, 165 (99.4%) underwent allotransplantation. Acute graft-versus-host disease (GVHD, grades II to IV) developed in 76 patients. Conditioning regimens before HSCT include total body irradiation (n=57), busulfan (n=80), and reduced intensity (n=29). Forty-five (27.1%) had thyroid dysfunction during 3 months after HSCT (29 euthyroid sick syndrome [ESS], 6 subclinical hyperthyroidism, 4 subclinical hypothyroidism, 3 hypothyroxinemia, 2 overt hyperthyroidism, and 1 high T4 syndrome). In a univariate logistic regression analysis, age at HSCT (P=0.002) and acute GVHD (P=0.009) had statistically significant relationships with thyroid dysfunction during 3 months after HSCT. Also, in a univariate logistic regression analysis, ESS (P=0.014) showed a strong statistically significant association with mortality.ConclusionIn our study 27.1% patients experienced thyroid dysfunction during 3 months after HSCT. Increase in age and acute GVHD may be risk factors for thyroid dysfunction during 3 months after HSCT. There was a significant association between ESS and mortality.